PARIWISATA BALI DALAM HIMPITAN DIALETIKA BUDAYA - I Ketut Manik Astajaya (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2019)
The development of Bali Tourism has implications for the process of cultural transformation and cultural change. In the perspective of cultural dialectics, changes occur largely in the outer structure, whereas in the damal structure it is clear that there is continuity and preservation of culture; (2) The development of tourism, especially the type of tourism developed in Bali, essentially brings the Balinese people squeezed between the two poles of power. On the one hand, they are obliged to maintain their cultural traditions and customs which are commodities that can be 'sold' in tourism. On the other hand, tourism sometimes collides local culture with the modern world. This provides a great opportunity because of the unpreparedness of the community, resulting in local culture with the modern world. This provides local will be swept away in the swift waves of global culture. Phases of local people's attitudes towards tourism start from: (1) Eupharia, which is sympathy because people have high hopes for the development of tourism; (2) Apathy, which is starting to disturb his life because of social disparities as a result of tourism development; (3) Annoyance, that is, people are getting bored and even people feel disturbed by the existence of tourism; and (4) Antagonism, which has begun to openly show its displeasure with the existence of tourism.Keywords: Bali, Tourism, Dialetika Culture